Enhancing Lecturer Performance: The Power of Leadership, Culture, and Governance - Manuhutu, Meldi; Rahardjo, Kusdi; Eko Nurtjahjono, Gunawan (Profit: Jurnal Adminsitrasi Bisnis, 2024)
Since the higher education quality gap between Western Indonesia and Eastern Indonesia is entirely high, especially in Papua and West Papua (known as the LLDIKTI 14 region), evaluating lecturer performance in that region is necessary. This study aims to explain and analyze the impact of transformational leadership, organizational culture, and good university governance on lecturer motivation and performance at Victory Sorong University and Nani Bili Nusantara University. This research is a quantitative explanatory study, with the population of all lecturers at both universities, utilizing a probability sampling technique with a saturated sample of 115 lecturers. The results indicate that organizational culture and good university governance positively and significantly affect work motivation, while transformational leadership has a positive but insignificant effect. Organizational culture and work motivation also positively and significantly affect lecturer performance, while transformational leadership and good university governance have a positive but insignificant effect.